Geochemical Evidence of Island-Arc Origin for Sumatra Island; A New Perspective based on Volcanic Rocks in Lampung Province, Indonesia - Zulkarnain, Iskandar (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i4.128Since decades, Sumatra Island is considered as the Eurasia continental margin where the Indian Ocean plate has been subducted oblique beneath the continental plate of Sumatra. But, the occurrences of volcanic rocks in almost all areas of Lampung Province in the southernmost of Sumatra Island, as the presence of the Quaternary Tanggamus Volcano in the western part of the province together with the Quaternary Rajabasa Volcano in the eastern area cannot be justified using the consideration. Spider diagrams of trace and rare earth elements of volcanic rocks from the western and eastern areas of the province reveal that the rocks come from three different tectonic settings, namely island-arc, active continental margin (ACM), and intra continental plate. All basalt and one dacite of western volcanic rocks show a character of island-arc origin, while the eastern volcanic rocks are reflecting characters of ACM and intra continental plate. Plot of the rocks in the diagram of Ta/Yb versus Ce/P and in Ta/Yb versus Th/Yb confirmed the tectonic environments and specifically classify the intra continental plate into Within Plate Volcanic Zone (WPVZ). The island-arc group is characterized by Ta/Yb ratio of less than 2.0 and Ce/P less than 1.8. The ACM group is recognized having Ta/Yb ratio between 2 and 4 with Ce/P more 1.8, while the WPVZ group is defined as a group having Ta/Yb more than 6 and Ce/P more than 1.0. The result indicates that the western part of Sumatra is an island-arc fragment and the eastern part belongs to the Eurasia continental margin. The concentration of volcanics having ACM character from areas around the Sumatra Fault System to the east indicates that the collision zone between the Sumatra island-arc fragments with the Eurasia continental margin is probably located along the SFS. More statistical data is still needed from other Sumatra volcanics to confirm this conclusion.